2019
DOI: 10.3389/fcimb.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Leishmania amazonensis Infection Altered miR-294, miR-30e, and miR-302d Impacting on Tnf, Mcp-1, and Nos2 Expression

Abstract: Leishmaniases are neglected diseases that cause a large spectrum of clinical manifestations, from cutaneous to visceral lesions. The initial steps of the inflammatory response involve the phagocytosis of Leishmania and the parasite replication inside the macrophage phagolysosome. Melatonin, the darkness-signaling hormone, is involved in modulation of macrophage activation during infectious diseases, controlling the inflammatory response against parasites. In this work, we showed that exogenous melatonin treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 102 publications
2
37
1
6
Order By: Relevance
“…Our group showed that L. amazonensis induces upregulation of miR-294-3p and miR-721 in BALB/c-BMDM, which binds to Nos2 3′UTR, reducing the levels of NOS2 and NO production and increasing infectivity [61]. Also, miRNAs that are deregulated during infection, such as miR-30e and miR-302d, interfere with Nos2 mRNA expression and NO production; miR-294 and miR-302d regulate Tnf mRNA levels and miR-294 alters Ccl2/Mcp-1 mRNA, implicating the expression of these miRNAs in controlling infectivity [80]. Indeed, for a set of miRNAs, let-7a, miR-25, miR-26a, miR-132, miR-140, miR-146a, and miR-155, their upregulation in L. major-infected human macrophages was negatively correlated with the Once the parasites are phagocytized by these immune cells, they are differentiated into amastigote forms and begin to multiply within those cells.…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group showed that L. amazonensis induces upregulation of miR-294-3p and miR-721 in BALB/c-BMDM, which binds to Nos2 3′UTR, reducing the levels of NOS2 and NO production and increasing infectivity [61]. Also, miRNAs that are deregulated during infection, such as miR-30e and miR-302d, interfere with Nos2 mRNA expression and NO production; miR-294 and miR-302d regulate Tnf mRNA levels and miR-294 alters Ccl2/Mcp-1 mRNA, implicating the expression of these miRNAs in controlling infectivity [80]. Indeed, for a set of miRNAs, let-7a, miR-25, miR-26a, miR-132, miR-140, miR-146a, and miR-155, their upregulation in L. major-infected human macrophages was negatively correlated with the Once the parasites are phagocytized by these immune cells, they are differentiated into amastigote forms and begin to multiply within those cells.…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
“…Our group showed that L. amazonensis induces upregulation of miR-294-3p and miR-721 in BALB/c-BMDM, which binds to Nos2 3 UTR, reducing the levels of NOS2 and NO production and increasing infectivity [61]. Also, miRNAs that are deregulated during infection, such as miR-30e and miR-302d, interfere with Nos2 mRNA expression and NO production; miR-294 and miR-302d regulate Tnf mRNA levels and miR-294 alters Ccl2/Mcp-1 mRNA, implicating the expression of these miRNAs in controlling infectivity [80].…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
“…2019, 20, 6248 2 of 20 forms found in the proboscis of the phlebotomine sand fly host, to amastigote forms in the interior of macrophage phagolysosomes in the mammalian host [3]. Leishmania infection results in the regulation of pathways that are involved in the inflammatory response and leishmanicidal mechanisms, such as nitric oxide (NO) production via nitric oxide synthase 2 (NOS2), which is induced by Th1-cytokines [4][5][6][7][8][9]. However, Leishmania can subvert these mechanisms, which impacts on Th1/Th2 cytokine balance and induces macrophage arginase 1 (ARG1) activity to produce polyamines, putrescine, spermidine, and spermine, leading to Leishmania survival [6,[10][11][12].L-arginine is an essential amino acid and a precursor in the synthesis of proteins, urea, ornithine, citrulline, NO, creatinine, agmatine, glutamate, proline, putrescine, spermidine, and spermine, supporting the proline, glutamate, and polyamine metabolism at the whole organism level or cellular level in mammals.…”
mentioning
confidence: 99%
“…) regulates T-cell differentiation and plasticity during VL Infection (Pandey et al, 2016). It was also reported that inhibition of miR-181c-5p, miR-294-3p, miR-30e-5p, and miR-302d-3p reduces the infectivity of Leishmania amazonensis by modulation of Nos2, Tnf, Mcp-1/Ccl2, and RANTES/Ccl5 mRNA expression (Fernandes et al, 2019). Regulation of TGF-β by differentially expressed miRNAs may modulate host immune responses; the rapid onset and termination of diverse effector mechanisms must be efficiently controlled to prevent the adverse consequences of excessive inflammation or pathogenesis.…”
Section: Discussionmentioning
confidence: 96%